Analisis Efektivitas Bantuan Langsung Tunai dalam Mencegah Angka Kemiskinan - Selpiani Selpiani; Ahsan Putra Hafiz; Kurniati Kurniati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the effectiveness of Direct Cash Assistance (BLT) in preventing poverty in the village of Sungai Jering. The background of this research problem is the high poverty rate, which is a major challenge for local governments in improving community welfare. The BLT program is expected to provide direct economic support to poor and vulnerable families. The theoretical concepts underlying this research include transparency, community participation, supervision, justice, and social security. The research method used is qualitative, allowing researchers to understand phenomena holistically and deeply. Data were collected through in-depth interviews, observations, and document analysis involving BLT beneficiaries and other related parties. The results of the study show that the BLT program in Sungai Jering has succeeded in increasing the purchasing power of the community and providing economic stability for recipient families. This success is marked by active community participation in the monitoring and implementation of the program, as well as high transparency in the distribution of assistance. However, to improve the program's effectiveness, support in the form of long-term sustainable economic empowerment programs is needed. In conclusion, BLT can be an effective tool in poverty alleviation strategies if implemented well, with high accountability and strong community involvement. With the right policies, this program is expected to become a model for other villages in managing social assistance effectively.